Food policy in a complex, changing world: Event synopsis - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
Food policy—at global, regional, national, and local levels —operates in an increasingly complex world that is changing faster than ever. In the past several decades, many important food policy questions have been answered and challenges have been overcome. Since its founding in 1975, the International Food Policy Research Institute (IFPRI) itself has been instrumental in producing rigorous, policy-relevant research to improve the lives of hungry and malnourished people. IFPRI helped make the case that agriculture, as a driver of poverty reduction and broadbased economic growth, requires investment. It helped explode the myth that the Green Revolution technologies benefited only large-scale farmers and showed that agricultural growth has powerful spillover effects. It highlighted the role of gender, both in society and within households, in improving food security and nutrition. And IFPRI continues to work closely with countries to support strategies and find on-the-ground policy solutions.